Importance of regular lifestyle with daytime bright light exposure on circadian rhythm sleep-wake disorders in pervasive developmental disorders - Nana N. Takasu; Motomi Toichi; Wataru Nakamura (Elsevier, 2011)
Considerable attention has been paid to individuals showing social maladjustment as well as withdrawal from social situations and activity, a state referred to as "Hikikomori" in Japanese. Recently, social maladjustment and Hikikomori states have also been noted to be highly prevalent among individuals with pervasive developmental disorders (PDDs), which involve abnormalities in social interactions and communication. The individuals with PDDs report a tendency to sleep and wake at irregular or inappropriate times and to suffer from sleep disorders by nature, and they tend to sleep at extreme late night or during the day while experiencing social maladjustment and Hikikomori states. Therefore, it is probable that their oral hygiene might deteriorate due to a circadian rhythm disorder, such as an abnormal salivary secretion rhythm or refusals and noncooperation of dental care due to mood/emotional and social problems, underlying and caused by their sleep and wake patterns. In this review, we describe the importance of regular lifestyle, especially regular sleep-wake rhythm with appropriately timed bright light exposure during daytime, for management of oral health in PDDs via improving their circadian rhythm disorders.